2013
DOI: 10.1017/s1466252312000229
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficilein foods and animals: history and measures to reduce exposure

Abstract: Many articles have summarized the changing epidemiology of Clostridium difficile infections (CDI) in humans, but the emerging presence of C. difficile in foods and animals and possible measures to reduce human exposure to this important pathogen have been infrequently addressed. CDIs have traditionally been assumed to be restricted to health-care settings. However, recent molecular studies indicate that this is no longer the case; animals and foods might be involved in the changing epidemiology of CDIs in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 179 publications
(276 reference statements)
4
60
1
8
Order By: Relevance
“…(ROLLAND et al, 1997). C. difficile has been reported in few other wild species, and it seems to be more common in synanthropic rodents and in captive animals under antibiotic therapy (SILVA et al, 2013;JARDINE et al, 2013;RODRIGUEZ-PALACIOS et al, 2013;HIMSWORTH et al, 2014;SILVA et al, 2014a;SILVA et al, 2014b). As this was not the case in the present study, the absence of C. difficile in the sampled animals was not a surprise.…”
supporting
confidence: 41%
See 1 more Smart Citation
“…(ROLLAND et al, 1997). C. difficile has been reported in few other wild species, and it seems to be more common in synanthropic rodents and in captive animals under antibiotic therapy (SILVA et al, 2013;JARDINE et al, 2013;RODRIGUEZ-PALACIOS et al, 2013;HIMSWORTH et al, 2014;SILVA et al, 2014a;SILVA et al, 2014b). As this was not the case in the present study, the absence of C. difficile in the sampled animals was not a surprise.…”
supporting
confidence: 41%
“…Despite the known importance of NHP as reservoirs of human pathogens, there are few studies focusing specifically on capuchin monkeys (BATISTA et al, 2013;ROCHA et al, 2015). Silva et al Clostridium difficile is a major nosocomial pathogen in humans and causes diarrhea and enterocolitis in domestic animals (RODRIGUEZ-PALACIOS et al, 2013). There are few studies about this enteropathogen in wild animals, but confirmed cases of C. difficile infection (CDI) have been reported in some species (BOJESEN et al, 2006;SILVA et al, 2013).…”
mentioning
confidence: 99%
“…However, in recent years C. difficile infection (CDI) is increasingly common in the community, in younger patients without a previous history of hospitalisation or antibiotic treatment (Gupta and Khanna 2014). Studies worldwide have reported the presence of the bacterium in animals and foods (Songer and Anderson 2006;Hoover and Rodriguez-Palacios 2013;Rodriguez-Palacios et al 2013) with a prevalence that varies according to the methodology used, the geographical area, the age and the animal species studied. While C. difficile is well known as enteric pathogen in some food producing, wild and companion animal species (Donaldson and Palmer 1999;Songer and Uzal 2005), there are several reports describing the presence of the bacterium in the intestinal contents of apparently healthy animals (Rodriguez et al 2012;Hawken et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…difficile is an enteric pathogen of companion animals (cats, dogs, horses) and food animals (cattle, sheep, goats, pigs) 13,14 . Neonates are typically colonised with C. difficile due to the lack of colonisation resistance afforded by mature intestinal microflora; hence prevalence decreases with age 15,16 .…”
Section: Difficile In Animals and Foodmentioning
confidence: 99%